Association of GDP, National Healthcare Expenditure and Participation in National Cancer Screening Programmes with Mortality from Cancer and Cardiovascular Diseases in the EU Countries - Leško, Anamaria (Digital Repository of Theses, 2026)
There is complex association of GDP, national healthcare expenditure and participation in national cancer screening programmes with mortality from cancer and cardiovascular diseases. The focus of this mix-method (quantitative and qualitative) research based on relevant open-source secondary data, is a comprehensive study on the association of GDP, national healthcare expenditure and participation in national cancer screening programmes with mortality from cancer and cardiovascular diseases in the 27 EU countries. Some of the key findings indicate a strong collective significant effect of GDP and participation in colorectal cancer screening test to total colorectal cancer mortality among the EU countries; a moderate collective significant effect of national healthcare expenditure and participation in cervical cancer screening test to total cervical cancer mortality among the EU countries; a moderate collective significant effect national healthcare expenditure and participation in colorectal cancer screening test to total colorectal cancer mortality among the EU countries. Also, valuable research-based business-related recommendations for healthcare industry were provided in terms of early detection technology, wearables technology, tobacco cessation, obesity management, commercial partnerships, partnerships with employee resource groups, high-performance computing, and increased AI-driven solutions. Future studies should address these limitations by incorporating multilevel, longitudinal datasets and adjusting for confounding variables to clarify the relationship between screening participation and breast cancer mortality. Keywords: economy, public health, prevention, Europe, business